2004
DOI: 10.1001/archderm.140.7.805
|View full text |Cite
|
Sign up to set email alerts
|

Are Patients With Psoriasis Susceptible to the Classic Risk Factors for Actinic Keratoses?

Abstract: Background: An increased prevalence of benign solar damage (eg, facial wrinkles) but not neoplastic lesions was observed among patients with psoriasis who were exposed to Dead Sea climatotherapy compared with controls. Objectives: To compare the prevalence of actinic keratosis in psoriatic patients and controls and to assess whether known risk factors behave similarly in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(35 reference statements)
0
8
1
1
Order By: Relevance
“…We have examined this finding in greater detail in a separate publication and concluded that psoriasis may confer protection against actinic keratosis. 8 Our results do not confirm the findings of Frentz et al, 7 who reported that the risk of NMSC among Danish patients with psoriasis treated at the Dead Sea is increased almost 5-fold compared with the Danish general population. It should be stressed that the authors were unable to delineate why patients undergoing DSC develop skin cancer, because of the design of their study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We have examined this finding in greater detail in a separate publication and concluded that psoriasis may confer protection against actinic keratosis. 8 Our results do not confirm the findings of Frentz et al, 7 who reported that the risk of NMSC among Danish patients with psoriasis treated at the Dead Sea is increased almost 5-fold compared with the Danish general population. It should be stressed that the authors were unable to delineate why patients undergoing DSC develop skin cancer, because of the design of their study.…”
Section: Discussioncontrasting
confidence: 99%
“…Details of recruitment and methods have also been reported in a companion study. 8 All participants provided signed informed consent. The protocol was approved by the institutional review boards at all participating hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…Nickoloff uncovered a discription in the 19th century made by a distinguished British surgeon, Dr. Hutchinson, who concluded that the anatomical sites in which arsenic keratosis and SCC developed in psoriatic patients who had been treated with potassium arsenite did not include those at which psoriatic plaques developed [71,72]. In Nickoloff's reviews, he pointed out that PUVA-induced skin abnormalities generally spare psoriatic plaques and also referred to a recent study by others that psoriasis confers protection against actinic keratosis [73]. He implied that the tumor resistant phenotype of psoriatic plaques might be attributed to the tumor suppressive pathway involving a putative senescence-switch within the psoriatic keratinocytes [71].…”
Section: Resultsmentioning
confidence: 99%
“…Psoriasis lesions hardly ever progress to skin cancer despite chronic inflammation that often is a risk factor for cancer [6], [7]. Both psoriasis and skin cancer are characterized by uncontrolled KC proliferation in addition to angiogenesis and inflammation.…”
Section: Introductionmentioning
confidence: 99%